2020
DOI: 10.21037/tp.2019.09.10
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes of preterm infants: a recent literature review

Abstract: Background: Over the past several decades, improvements in technology in the Neonatal Intensive Care Unit (NICU) have led to improved survival of preterm infants. Some studies have found that premature infants are at higher risk of behavioral problems, motor and sensory abnormalities, developmental delay, and poorer academic performance, while other studies have found no significant difference.Methods: A literature search was conducted through PubMed for articles published between January 2018 and September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 19 publications
0
84
0
6
Order By: Relevance
“…Among biomedical factors, gestational age or birth weight were found to have a predictive effect on language delay, and the risk of suffering language impairments [9,10,23,37,38]. Other authors, however, have suggested that neurobehavioral outcomes at an early school age can be predicted based on IVH incidence as opposed to birth weight or GA [39].…”
Section: Introductionmentioning
confidence: 98%
“…Among biomedical factors, gestational age or birth weight were found to have a predictive effect on language delay, and the risk of suffering language impairments [9,10,23,37,38]. Other authors, however, have suggested that neurobehavioral outcomes at an early school age can be predicted based on IVH incidence as opposed to birth weight or GA [39].…”
Section: Introductionmentioning
confidence: 98%
“…Despite the prematurity, our neonatal survival rate was 100%. Nevertheless, preterm birth is associated with an increased risk for adverse neurodevelopmental outcomes [19]. Therefore, considerations on fetal maturity and a delay of a potentially curative maternal treatment should be carefully made in a multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…A preterm newborn (PTNB) is the one born before 37 weeks gestation, considering that a normal gestation lasts for 280 ± 15 days [1]. Depending on the gestational age, PTNB can be classified as extremely preterm (<28 gestational weeks), very preterm (28 ≥ 32 gestational weeks), moderately preterm (32-33 gestational weeks) and late preterm (34-36 gestational weeks) [2,3]. In addition, according to the weight at birth, newborns can be classified into low weight (<2500 g), very low weight (<1500 g) and extremely low weight (<1000 g) [4].…”
Section: The Preterm Newbornmentioning
confidence: 99%